Thin film encapsulation for quantum dot light-emitting diodes using a-SiNx:H/SiOxNy/hybrid SiOx barriers - Lim, Keun Yong; Kim, Hong Hee; Noh, Ji Hyun; Tak, So Hyun; Yu, Jae-Woong; Choi, Won Kook (ROYAL SOC CHEMISTRY, 2022)
A facile thin film encapsulation (TFE) method having a triple-layered structure of a-SiNx:H/SiOxNy/hybrid SiOx (ASH) on QD-LEDs was performed utilizing both reproducible plasma-enhanced chemical vapor deposition (PECVD) and simple dip-coating processes without adopting atomic layer deposition (ALD). The ASH films fabricated on a polyethylene terephthalate (PET) substrate show a high average transmittance of 88.80% in the spectral range of 400-700 nm and a water vapor transmission rate (WVTR) value of 7.3 x 10(-4) g per m(2) per day. The measured time to reach 50% of the initial luminance (T-50) at initial luminance values of 500, 1000, and 2000 cd m(-2) was 711.6, 287.7, and 78.6 h, respectively, and the extrapolated T-50 at 100 cd m(-2) is estimated to be approximately 9804 h, which is comparable to that of the 12 112 h for glass lid-encapsulated QD-LEDs. This result demonstrates that TFE with the ASH films has the potential to overcome the conventional drawbacks of glass lid encapsulation.